THE ANALYSES OF THE SPORT INJURIES DISTRIBUTION IN AMATEUR AND PROFESSIONAL FOOTBALL PLAYERS ACCORDING TO AGE GROUPS AND BODY MASS - Gündoğdu, Cemal; Özmerdivenli, Recep (Gazi Üniversitesi, 2003)
This study was performed to analyze the sport injuries distribution according to age and body mass categories on participating two hundred sportsmen that they were playing in amateur and professional football team in Elaz›g and Malatya. Questionnaire was applied to footballers including question related with injuries and medical treatment. All the registered and non-registered injuries of footballers were taken into consideration. Also, questioning was done to determine the injuries rates in trainings and football match. SPSS statistical program were made used of to evaluate the answer to questionnaire. Chi-square (X2) test was used for evaluating the data. Statistical significance was defined as (p<0.05). Statistical meaningful differences was found in turns of injuries proportion of registered and unregistered in training and match between amateur and professional footballers (p<0.05). Injury dispersions according to number of in this study was examined and there were ascertained differences between age groups and disability dispersions but this differences was not statistical meaningful. In addition to this, there is no statistical difference between body mass weight of subject and injury dispersions (p>0.05).In conclusion, it can be say that it is necessary to register all types of injury and evaluate. To eliminate the factors reasons to injury in amateur and professional footballers who are exposed to high injury rates must be cooperation among doctor of medicine, coach and sportsman and also necessary education program must be prepared and practiced.

Bu çalışma; amatör ve profesyonel futbolculardaki spor sakatlıklarının vücut kütlesi ve yaş gruplarına göre dağılımlarının analizini yapmak üzere, Elazığ ve Malatya’da amatör ve profesyonel takımlarda futbol oynayan 200 sporcunun katılımı ile gerçekleştirildi.Futbolculara sakatlıkları ve sakatlık sonrası tedavilerine ilişkin soruların yer aldığı anket uygulandı. Futbolcuların kayıtlara girmiş ve kayıtlara girmemiş sakatlıklarının tamamı değerlendirmeye alındı. Ayrıca antrenman ve maçlardaki sakatlanma oranları sorgulandı. Anketlerden elde edilen cevapların istatistiksel değerlendirilmesinde SPSS paket programından yararlanıldı. Elde edilen bulgular (x2) kare testi ile değerlendirildi. ‹statistiksel anlamlılık düzeyi p< 0. 05 olarak seçildi. Amatör ve profesyonel futbolcular arasında, tıbbi kayıtlara giren ve girmeyen, antrenman ve maçlardaki sakatlanma oranları açısından istatistiksel olarak anlamlı fark bulundu (p<0.05). Denek sayılarına göre sakatlık dağılımlarının incelenmesi sonucunda yaş grubu ile sakatlık dağılımlarının farklı olduğu ancak farkın istatistiksel olarak anlamlı düzeye ulaşmadığı, aynı şekilde deneklerin vücut kütleleri ile sakatlık dağılımları arasın-da istatistiksel olarak anlamlı bir farkın olmadığı görüldü (p>0.05).  Sonuç olarak; Amatör ve profesyonel futbolcularda sakatlanma oranının yüksek olduğu ve futbolculardaki sakatlanmaya neden olan faktörlerin ortadan kaldırılması için hekim, antrenör ve sporcuların işbirliği yapmalarının sağlanması, gerekli eğitim programlarının hazırlanarak uygulanmaya konulması ve her tür sakatlığın kayıt altına alınarak değerlendirilmesi gerektiğini söylenebilir.
AMATÖR VE PROFESYONEL FUTBOLCULARDAKİ SPOR SAKATLIKLARININ VÜCUT KÜTLESİ VE YAŞ GRUPLARINA GÖRE DAĞILIMLARININ ANALİZİ